2017
DOI: 10.1186/s13287-017-0509-2
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic adipose-derived stem cell therapy overcomes ischemia-induced microvessel rarefaction in the myocardium: systems biology study

Abstract: BackgroundMyocardial microvascular loss after myocardial infarction (MI) remains a therapeutic challenge. Autologous stem cell therapy was considered as an alternative; however, it has shown modest benefits due to the impairing effects of cardiovascular risk factors on stem cells. Allogenic adipose-derived stem cells (ASCs) may overcome such limitations, and because of their low immunogenicity and paracrine potential may be good candidates for cell therapy. In the present study we investigated the effects of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
(66 reference statements)
1
18
0
Order By: Relevance
“…Pigs have consequently been broadly used to evaluate novel vascular therapies. 46 Recent studies include the intracoronary administration of pASCs after an acute myocardial infarction model [47][48][49] and the transplantation of pASCs cell sheets in a porcine model of chronic heart failure. 50 The structures of porcine and human skin are similar, making pigs a suitable model for dermatologic preclinical studies.…”
Section: Applications In Preclinical Modelsmentioning
confidence: 99%
“…Pigs have consequently been broadly used to evaluate novel vascular therapies. 46 Recent studies include the intracoronary administration of pASCs after an acute myocardial infarction model [47][48][49] and the transplantation of pASCs cell sheets in a porcine model of chronic heart failure. 50 The structures of porcine and human skin are similar, making pigs a suitable model for dermatologic preclinical studies.…”
Section: Applications In Preclinical Modelsmentioning
confidence: 99%
“…MSCs are known to be one source of TGF-β1 [ 14 15 ], but whether TGF-β1 secreted by MSCs exhibit potent immunosuppressive activity remains unknown. To address this issue, we isolated MSCs from WT or TGF-β1 +/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…The cardiac regenerative capacity of MSCs has been explored in several small 81,[123][124][125] and large animal 32,126-134 models of heart disease, including acute and chronic ischemic cardiomyopathies. Autologous, 127,129 allogeneic, 32,82,128 or xenogeneic 135,136 MSCs have been studied, using different routes of administration, including intracoronary, 129,[131][132][133][134]137 transendocardial, 32,128,135 systemic, 124 and intravenous. 43,125,132 Most of these approaches support that MSC therapy, regardless of source, is effective at reducing scar size and improving left ventricular ejection fraction (LVEF).…”
Section: Mscs For Cardiac Repair Preclinical Studiesmentioning
confidence: 99%
“…Autologous, 127,129 allogeneic, 32,82,128 or xenogeneic 135,136 MSCs have been studied, using different routes of administration, including intracoronary, 129,[131][132][133][134]137 transendocardial, 32,128,135 systemic, 124 and intravenous. 43,125,132 Most of these approaches support that MSC therapy, regardless of source, is effective at reducing scar size and improving left ventricular ejection fraction (LVEF). Specifically, a meta-analysis of 52 preclinical animal studies of cell therapy for ischemic heart disease 138 suggested that MSC therapy is safe and associated with moderate ($7.5%) but significant improvements in LVEF.…”
Section: Mscs For Cardiac Repair Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation